Study protocol for a systematic review of evidence for digital interventions for comorbid excessive drinking and depression in community-dwelling populations - Eileen F S Kaner; Bernd Schulte; Fiona Beyer; Christiane S Schmidt; Amy O'Donnell (BMJ Open)
Introduction Excessive drinking and depression are frequently comorbid and make a substantial contribution to the global non-communicable disease burden. A range of effective interventions and treatments exist for either excessive drinking or depression alone, including a positive emerging evidence base for the use of digital interventions. Computerised and/or smartphone delivered advice could provide flexible, coordinated support for patients with comorbid excessive drinking and depression. However, to date, no systematic review of the evidence has been conducted focused on the effectiveness of digital interventions for this specific comorbid population. This systematic review will identify and evaluate the effectiveness of digital interventions for reducing comorbid excessive drinking and depression in community-dwelling populations.Methods and analysis We will search MEDLINE, The Cochrane Library, CENTRAL, CINAHL, PsycINFO, ERIC and SCI from inception to end of July 2019 for randomised controlled trials that evaluate any personalised digital intervention for comorbid excessive drinking and depression and published in any language. Primary outcomes will be changes in quantity of alcohol consumed and depressive symptoms. Screening, data extraction and risk of bias assessment will be undertaken independently by two reviewers, with disagreements resolved through discussion. Meta-analytic methods will be used to synthesise the data collected relating to the primary outcomes of interest.Ethics and dissemination As a systematic review, ethical approval is not needed. Findings will be published in peer-reviewed journals and presented at conferences.Trial registration number CRD42019130134.